Concept of Jihād: A Comparative Study of Dr. Tahir-Ul-Qadrī And Javed Ahmad Ghāmdī’s Thought - Muḥammad Iqbal Awan,Hafiz Umair Gulzar (AL-IDRAK JOURNAL, 2022)
Allah the Almighty has sent thousands of Prophets for the guidance of mankind. All the Prophets have propagated the message of Allah to their nations. Holy Prophet Muhammad peace be upon him is the last and final messenger of Allah in this world and Islam is the final message for the world. Allah the Almighty has given number of instructions for the propagation of His message. Jihad is one of them in this article the concept of Jihad of two eminent scholars of present era will be discussed in the detail.